International personal selling and real estate : complications and opportunities - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
This case study investigates the different factors that must be considered by individuals and businesses wishing to market real estate and property on an international basis. For example, methods of communication, government restrictions or cultural differences in the terms of property ownership may present unique challenges.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). International Personal Selling and Real Estate: Complications and Opportunities. In International marketing (pp. 513-514). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Real estate business -- Case studies; Real property -- Foreign ownership -- Case studies; Export sales contracts -- Case studies; Export marketing -- Case studies